Biomechanical conditions of maintaining balance in snowboarding - Staniszewski, M. (The Journal of Sports Medicine and Physical Fitness, 2019)
Snowboarding, along with Alpine skiing, is one of two most popular winter sports. While there are many studies on the mechanical conditions of movement in skiing, there is a lack of studies analyzing the forces affecting snowboarders. The difference in body orientation between snowboarding and skiing means that applying the same biomechanical rules to both sports is unjustified and a separate analysis is needed. The most difficult aspect of snowboarding is maintaining the correct body balance which is dependent on the directions and magnitudes of external forces and their torques. Therefore, the aim of this study was to analyze the forces that affect a snowboarder on the slope and the effects of these forces on the maintenance of a stable body posture. The research method used in the work is based on the theoretical analysis of physical phenomena that occur during riding on the snowboard. The study describes the biomechanical conditions that allow the snowboarder to maintain an upright posture when standing and moving, as well as the forces that initiate movement and decelerate the snowboarder. The physical forces that appear when moving forward and along an arc are analyzed, as are the mechanical interdependences that enable effective snowboarding. Knowing the rules of forces action is the best method for understanding how a snowboarder move and keep the balance on a slope. The application of theoretical knowledge should improve not only the self-confidence and effectiveness of the snowboarders but also the safety of their riding.